2006
DOI: 10.1021/jp066036g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the NCO + HCNO Reaction

Abstract: The kinetics of the NCO + HCNO reaction were studied using infrared diode laser absorption spectroscopy. The total rate constant was measured to be k(1) = (1.58 +/- 0.20) x 10(-11) cm(3) molecule(-1) s(-1) at 298 K. After detection of products and consideration of secondary chemistry (primarily O + HCNO and CN + HCNO), we conclude that NO + CO + HCN is the major product channel (phi = 0.92 +/- 0.04), with a minor contribution (phi = 0.04 +/- 0.02) from CO2 + HCNN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 70%
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 70%
“…Our previous studies [2][3][4][5][6] show that HCNO is a highly reactive molecule. Many secondary reactions following the photolysis can therefore occur.…”
Section: Resultsmentioning
confidence: 97%
“…The rate of the rise is primarily determined by the rate of collisional relaxation of a nascent vibrational distribution to a Boltzmann distribution. The buffer gas (CF 4 or SF 6 ) [4,5] was used to maximize this relaxation rate. Our product yield measurements assume that the detected products have reached a…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations